Impact of Public Debt Refinancing Techniques on Managing Public Budgeting in Iraq: An Analytical Study - Abdul Razaq Abdul Wahaab*, Noor; Hasan Ali, Azhar (Journal of Economics and Administrative Sciences, 2024)
The use of public debt by the state as a primary financial instrument is an essential strategy for directing economic activity, ensuring economic stability, and fostering economic growth. Despite this, as the levels of public debt continue to climb, governments are increasingly resorting to debt refinancing methods that are focused on either replacing or rescheduling current debt or converting to a new kind of creditor via investment and securitization investment vehicles to relieve the burden of their debt. Utilization of these instruments is essential for effective management of the overall budget. The discovery that debt scheduling and the debt sustainability index impact the accomplishment of fiscal surpluses and maximizing public revenues informed the study's results in Iraq, which inspired the conclusion that debt refinancing methods and general budget advice are connected. In order to reduce public debt with the possibility of eliminating it, to take advantage of the time it gives to initiate a strategy for investing in projects that contribute to increasing public revenues through which that debt can be repaid, to achieve sustainable economic growth, and to reduce the budgetary deficit, the author of the study recommended that the mechanism of scheduling public debt in its entirety and not just a part of its structure be implemented. Implementing the technique of scheduling public debt in its totality rather than simply a portion of its structure may help achieve these aims..